The Impact of the Covid 19 Pandemic on the Implementation of Construction Projects - Lukas Ris Indarto; Jati Utomo Dwi Hatmoko; Hery Suliantoro (Green Publisher Indonesia, 2025)
The construction industry is one of the industrial fields affected by the Covid 19 pandemic, many factors cause delays in the implementation experienced by construction projects. This study found that project productivity was the most affected factor due to the ongoing Covid pandemic, in addition to obtaining a total of 7 factors including high risk, 5 medium risk factors, and 1 low risk factor. As for the risk response, it has been recommended by the author to be covered in this journal in order to help readers in dealing with similar risks.